Teams Games Tournament Learning Model to Improve Elementary School Students' Mathematical Creative Thinking Skills - Udiani, Ni Made Puspita; Agustika, Gusti Ngurah Sastra; Kristiantari, Maria Goreti Rini (Thinking Skills and Creativity Journal, 2024)
The mathematical creative thinking skills of students are still relatively low and need to be improved. Thus, they need a learning model that can enhance their mathematical creative thinking skills. One of the solutions to this problem is the cooperative learning model using the Teams Games Tournament method. This research aims to analize the result of the Teams Games Tournament cooperative learning model on grade IV students' mathematical creative thinking skills. This study used a quasi-experimental design with a non-equivalent control group design. The population of this study consists of 251 students, selected using a cluster random sampling technique, with a description test used as the data collection method.  Data on mathematical creative thinking skills, obtained from post-test results, were analyzed with descriptive statistical techniques and inferential statistical analysis, specifically the polled variance t-test. The polled variance t-test resulted in tcount (4.73539) > ttable (1.67528) with 5% significance level. According to the test results, it can be concluded that the Teams Games Tournament cooperative learning model significantly affects the grade IV students' elementary school mathematical creative thinking skills. The TGT cooperative learning method can help students understand the concept of subject matter through solving real problems with daily life, peer tutor activities to deepen understanding of the material, playing games, and tournament activities.